2009
DOI: 10.1177/097133360902100104
|View full text |Cite
|
Sign up to set email alerts
|

Protestant Work Ethic Endorsement and Social Justice Values in Developing and Developed Societies

Abstract: Within the Western individualist model that has dominated approaches to "development" in most contemporary societies, an emphasis on personal ambition and individuated rights and freedoms is usually considered to be a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(56 reference statements)
0
7
1
Order By: Relevance
“…But no matter how important public information may be in straightening out misconceptions, western countries rest on a historically robust cultural belief in self‐determination. Citizens with this conviction are in general less inclined to back up social welfare and equality measures and more inclined to stress free enterprise and social Darwinism (31). And indeed, it has been shown that the propensity to attribute obesity to lack of willpower correlates strongly with classic Protestant values (14).…”
Section: Discussionmentioning
confidence: 99%
“…But no matter how important public information may be in straightening out misconceptions, western countries rest on a historically robust cultural belief in self‐determination. Citizens with this conviction are in general less inclined to back up social welfare and equality measures and more inclined to stress free enterprise and social Darwinism (31). And indeed, it has been shown that the propensity to attribute obesity to lack of willpower correlates strongly with classic Protestant values (14).…”
Section: Discussionmentioning
confidence: 99%
“…Higher power ethnic groups generally endorse the PWE more so than lower power ethnic groups (Beit-Hallahmi, 1979;Cokley et al, 2007;Cozzarelli, Wilkinson, & Tagler, 2001;Oyserman, Gant, & Ager, 1995; but see Monteith & Spicer, 2000;Tang & Tzeng, 1992). The same effect of group-based power is also true for socioeconomic status (Cokley et al, 2007;Frey & Powell, 2009;Tang & Tzeng, 1992). The evidence is not entirely clear for gender, with some studies showing that men endorse the PWE more so than women (Cozzarelli et al, 2001;Wentworth & Chell, 1997) and other studies showing no gender difference (Christopher & Mull, 2006;Furnham, 1987;Mirels & Garrett, 1971;Tang & Tzeng, 1992).…”
Section: Group-based Power and Endorsement Of Pwementioning
confidence: 87%
“…The PWE states that humans (rather than the divine) control their own destiny and emphasizes that people should work hard as the means to success (Mirels & Garrett, 1971). Many scholars view the PWE as the ideology that gave rise to modern Western capitalist societies (e.g., Weber, 1905Weber, /1958, and endorsement of the PWE no longer is associated with religious affiliation or involvement (Frey & Powell, 2009;McHoskey, 1994; but see Giorgi & Marsh, 1990;H. Jones, Furnham, & Deile, 2010).…”
Section: Protestant Ethic Versus Egalitarianismmentioning
confidence: 99%
See 1 more Smart Citation
“…This intertwining is well refl ected in the papers selected. From concerns of local justice (Mathew & Pellissery 2009) to linking issues of justice to social values (Powell 2009;Frey & Powell 2009), understanding reward and punishment allocations (Krishnan, Varma and Pandey 2009) and issues of justice in the case of the young (Sahoo & Suar 2009) presents a panorama of domains where justice and diversity concerns are salient.…”
Section: Facets Of Justicementioning
confidence: 99%